2019
DOI: 10.3390/polym11111849
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Layer Approach toward Self-Healing and Self-Cleaning Polyurethane Thermosets

Abstract: There is an urgent need for coatings that exhibit both self-healing as well as self-cleaning properties as they can be used for a wide range of applications. Herein we report a novel approach toward fabricating polyurethane thermosets possessing both self-cleaning and self-healing properties. The desired coating was achieved via casting a bottom layer of self-healable polyurethanes comprised of reversible phenolic urethane bonds followed by a subsequent dip-coating of the prepared layer in a solution of bis(3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In these cases, the self-healing could be readily controlled by adjusting the temperature. Various kinds of novel self-healing polyurea-based polymeric materials can be synthesized by this approach [ 69 , 70 , 71 ]. As a result, CAN polyurea-based materials are envisioned to have substantial applications in smart surfaces, smart electronics, and 3D printing [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the self-healing could be readily controlled by adjusting the temperature. Various kinds of novel self-healing polyurea-based polymeric materials can be synthesized by this approach [ 69 , 70 , 71 ]. As a result, CAN polyurea-based materials are envisioned to have substantial applications in smart surfaces, smart electronics, and 3D printing [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] One of the key focus is the use of benign polydimethylsiloxane (PDMS) as an alternative to PFAS because PDMS is known for imparting water and oil repellent properties while still acceptable for food contact applications. [16][17][18][19][20][21][22] In a recent breakthrough study, we reported the fabrication of water-and grease-resistant coating using Chitosan-grafted-PDMS (Chitosan-g-PDMS), and the coated paper was 100% recyclable by washing the coating off. 12 From a practical perspective, chitosan-g-PDMS system is relatively expensive while at the same time, chitosan has a low availability due to complicated purification processes.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently employed chemically modified chitosan in combination with silicone to provide substrates with both water and oil repellencies. In addition, we also used zein as a filler in a chitosan-graft-silicon oil formulation . Silicone oils are known to impart good water and oil repellencies to various coatings, such as urethanes and epoxies. However, silicone oils are expensive and also have some limitations. For example, above a certain limit, silicone oil is less safe for food contact applications.…”
Section: Introductionmentioning
confidence: 99%